A Supportive Social Environment Conducive to Learning is A Key Consideration for Parents when Choosing A Nature School in Klaten - Fatimah Nur Yuliawati; D Darsinah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The purpose of this study is to identify the factors considered by parents in choosing nature schools. The uniqueness of the study lies in exploring parents' interest specifically in nature-based education and focusing solely on nature schools. Methodelogy: This study uses a quantitative method with a descriptive approach. The population consists of 70 parents from three nature schools in Klaten Regency, and a sample of 60 parents was selected using proportional random sampling. Data were collected through direct questionnaire distribution and analyzed using descriptive data analysis with SPSS 25. Results: The results show that the factor with the highest average score is the social environment that supports the learning atmosphere, with an average score of 3.65. This indicates that positive interactions between teachers and children as well as among students are highly prioritized by parents. Meanwhile, the factor with the lowest score is accessibility and location (2.90), showing that ease of access is not a major consideration when choosing a nature school. Applications/Originality/Value: This study highlights parents' priorities in selecting nature schools and provides new insight by focusing exclusively on nature-based early childhood education settings. The findings can serve as a reference for nature schools to strengthen the social environment that supports learning, as this is the most influential factor for parents. The study also offers value for policymakers and educators by identifying which aspects are most critical in promoting and improving nature school quality.